Synthesis of Heterocyclic-Substituted Novel Hydroxysteroids with Regioselective and Stereoselective Reactions - Kolo, Abubakar Mohammed; Ipek, Emine; Capan, Irfan; Servi, Suleyman (Wiley, 2018)
Polyhydroxy steroids bearing the 3,5,6-trihydroxy pattern were synthesized from different heterocyclic-substituted unsaturated steroid by an easy and simple method with high yields. The endocyclic double bond of thiophene-substituted and quinoline-substituted steroids were converted to the trans-diaxial diol by the regioselective and stereoselective reactions with m-chloroperoxybenzoic acid in the basic medium.
Keywords: Prostate-Cancer; Biological Evaluation; Transition-State; Chiral Ketones; Epoxidation; Steroids; Agents; Galeterone; Design